Media Edukasi Kesehatan Gigi Berbasis Cerita Bergambar Digital: Pengembangan dan Uji Efektivitas pada Siswa Sekolah Dasar - Liasari, Ira; Priyambodo, R. Ardian; Jumriani, Jumriani; Nur Aida, Wanda; Nur Azizah, Putri (Jurusan Keperawatan Gigi Poltekkes Kemenkes Makassar, 2025)
Dental caries is a common oral health problem among elementary school children and is largely influenced by low levels of knowledge and improper tooth-brushing practices. This study aims to develop a digital picture storybook as an educational medium and to assess its feasibility and effectiveness in improving children’s knowledge of proper tooth-brushing techniques. The study employed a Research and Development (R&D) approach using the ADDIE model, which includes the stages of analysis, design, development, implementation, and evaluation. Product validation was conducted by material and media experts. Field testing was carried out with 30 students from grades III and IV at UPT SPF SDN Tamamaung, Makassar. Data were analyzed using the Shapiro–Wilk normality test and paired t-test. Material expert validation yielded a feasibility score of 75.56% (feasible), while media expert validation resulted in a score of 83.75% (highly feasible). Students’ responses regarding the media’s appearance and attractiveness showed a score of 95.3% (highly feasible). Pre-test and post-test data were normally distributed (p>0.05). The paired t-test results indicated a significant increase in knowledge following the educational intervention using the digital media (p<0.001). These findings indicate that the developed digital picture storybook is not only feasible but also effective in improving elementary school students’ knowledge of proper tooth-brushing techniques.